Nuclear Receptors 2010
DOI: 10.1007/978-90-481-3303-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors: Their Actions and Functional Roles in Health and Disease

Abstract: Abstract:Our view of estrogen signalling has undergone a paradigm shift over the recent 10-15 years with the discovery of a second estrogen receptor, ERβ, in 1995 and the finding that estrogens play an important role also in male physiology. Aromatase deficient patients and aromatase knock-out mice have highlighted the importance of estrogens in development and metabolic homeostasis while ER knock-out mice, ERα-/-and ERβ-/-, have shown that both ERs are of physiological importance and that ERα and ERβ have dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 496 publications
(445 reference statements)
0
47
0
Order By: Relevance
“…In more recent years, we have also learned that the effects of E2 can have a very rapid onset, within seconds to minutes. These effects may be mediated by membrane‐localized ERα and ERβ, respectively (after exposure to ligand stimuli), or by membrane receptors that are genetically and structurally unrelated to ERα and ERβ, for example, GPR30 (G‐protein coupled receptor 30) 1 , 2 , 3 , 4 (). The very rapid effects of E2 may include release of intracellular Ca 2+ and activation of calcium‐calmodulin‐dependent kinases or activation of other signal transduction pathways of the mitogen‐activated protein kinase family and phosphoinositide 3‐kinase.…”
Section: Basic Estrogen Receptor Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent years, we have also learned that the effects of E2 can have a very rapid onset, within seconds to minutes. These effects may be mediated by membrane‐localized ERα and ERβ, respectively (after exposure to ligand stimuli), or by membrane receptors that are genetically and structurally unrelated to ERα and ERβ, for example, GPR30 (G‐protein coupled receptor 30) 1 , 2 , 3 , 4 (). The very rapid effects of E2 may include release of intracellular Ca 2+ and activation of calcium‐calmodulin‐dependent kinases or activation of other signal transduction pathways of the mitogen‐activated protein kinase family and phosphoinositide 3‐kinase.…”
Section: Basic Estrogen Receptor Biologymentioning
confidence: 99%
“… 1 , 4 , 5 , 6 Each class of ER ligands induces a unique ER conformation, which promotes specific coregulator protein interactions and association of the ER N‐ and C‐terminal transcription activation functions, AF‐1 and AF‐2, respectively. 1 , 7 , 8 …”
Section: Basic Estrogen Receptor Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of ovariectomized rats with an ERb-selective agonist (ERB-041) had no significant effects on the mammary tissue, indicating that ERb-selective agonists are non-mammotrophic (Nilsson and Gustafsson, 2011). Female ERb knockout mice (bERKO) were reported to show a normal mammary gland development, while female aERKO mice showed impaired postpartum mammary development despite elevated levels of circulating estradiol (Nilsson and Gustafsson, 2010). However, the role of ERb is still not established because studies focusing on this isoform remain few in comparison to those on ERa.Tissue recombinant techniques conducted in mice concluded that stromal cell ERa expression might be essential for growth stimulation of the ductal mammary epithelium.…”
Section: Role Of Estrogens and Their Receptors In The Regulation Of Mmentioning
confidence: 99%
“…Effects of estrogen are mediated by not one but two distinct subtypes of estrogen receptors, ER alpha and ER beta [10]. The two receptors have differing affinities and responsiveness to various SERMs, and differing tissue distribution and effectiveness at various gene regulatory sites.…”
Section: Estrogen Receptor (Er) Alpha and Beta Subtypesmentioning
confidence: 99%